Utilization of alum sludge as chromium removal - Zahari N.M.; Sidek L.M.; Zulkifli M.A.A.; Hua C.K.; Jalil N.A. (American Institute of Physics Inc., 2023)
The amount of alum sludge produced at water treatment plant has become a problem where it is highly costly in order to dispose them. Various research was conducted to find the most suitable and economic alternative to recycle and reused of alum sludge. In this study, alum sludge was retrieved from Waterworks where it was dewatered, dried, grounded and sieved to obtain smallest particle sizes of alum sludge. The synthetic water was prepared at the laboratory in as it was used to imitate the properties of real water contaminated with chromium. This study was conducted to determine the percentage reduction of chromium concentration in synthetic water by using alum sludge as absorbent. The percentage reduction of chromium was observed under the effect of initial concentration of chromium and the height of alum sludge. The result indicates that chromium concentration reduction was the highest at the lowest initial concentration and at the highest height of alum sludge and vice versa. 2017 Author(s).